(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
The article, which addresses the War of the Pacific during its development in Tacna and Arica, aims to explain the construction of imaginaries towards Peru, Bolivia and Chile in the US press. The content analysis carried out on the newspapers allows us to conclude that the imaginary about Peru was damaged by the “morality” of its political-military leaders; that of Bolivia represented a poor and disorganized country; and that of Chile emerged as an ambivalent state: organized, but barbarous.